HUBUNGAN ANTARA WAKTU PAPARAN CHLORINE DIOXIDE GEL DAN ZONA HAMBAT PERTUMBUHAN BAKTERI Fusobacterium nucleatum PENYEBAB PENYAKIT PERIODONTAL - , RIZKI AMALIA FEBIANTI, Dr. drg. Ahmad Syaify, Sp. Perio (K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study was to know the relation between exposure time of Chlorine dioxide gel and the zones inhibition of growth Fusobacterium nucleatum bacteria the cause of periodontal disease. The method that used in this study was agar diffusion test with MHA (Mueller Hinton Agar) plate which had swabbed with Fusobacterium nucleatum. Six wells (diameter 6 mm) were made in plate then 4 wells dropped with Chlorine dioxide gel (50 µl), 2 wells dropped with Chlorhexidine digluconate 0,12% gel (50 µl) and Aquades sterile (50 µl). The plate were incubated for 48 hours and observed periodically at 12, 16, 22, 24 and 48 hours with temperature was put on 37ºC. The antibacterial activities of Chlorine dioxide gel were showed by zones of inhibition formation. The zones inhibition were measured across the diameter using sliding caliper in scale of 0,02 mm. Statistical analysis was carried out using a Spearman correlation test. The results of this study was obtained at -0,829 coefficient corelation with p= 0,000 (p<0,05) showed a significant association with negative direction, that an increase of time exposure followed by a decrease in bacterial zones inhibition. The results of the analysis with Bonferroni test showed a significants reduction in bacterial zones inhibition at observation time from 12 to 48 hours. The conclution of this study is there a relation between exposure time of Chlorine dioxide gel and the zones inhibition of growth Fusobacterium nucleatum bacteria the cause of periodontal disease.